Third Order Sandwich Results for Analytic Multivalent Functions Defined by Darweesh-Atshan-Battor Operator - Abbas, Arkan Firas; Atshan, Waggas Galib (Iraqi Journal of Science, 2025)
In the present work, by employing the differential subordination notion and Darweesh-Atshan-Battor operator, we investigate third-order of sandwich-type theorems for the p-valent of analytic functions.